Influence of charge carrier density, mobility and diffusivity on conductivitya-temperature dependence in polyethylene oxidea“based gel polymer electrolytes - Abdukarimov, Abdullaziz; Mohd Noor, Ikhwan Syafiq; Mamatkarimov, Odiljon; Mohd Arof, Abdul Kariem (SAGE Publications, 2021)
Determining the transport properties of charge carriers is essential to understand the factors that affect the conductivity trend of a polymer electrolyte system. In this work, charge carrier transport parameters of polyethylene oxide–based gel polymer electrolytes were estimated from fitting the Nyquist plot with the impedance equation, derived from the equivalent circuit that consists of a resistor in series with a constant phase element. The increase in electrolyte conductivity with temperatures from 303 K to 373 K is attributed to the increase of free ions, n (TPA+ cations and I¯ anions) and not to ionic mobility, μ. The decrease in μ with temperature is associated with the increase in the Stokes drag coefficient due to increase in ion collisions. This work explains how conductivity changes with number density of ions and mobility at various temperatures.